Development of vocabulary learning media using the Vlog now ‎application for eighth grade students of Bekunina private ‎Tsanawiyah School - Disa‎ Meirilci; Rahmawati Rahmawati; Musalwa Musalwa (Universitas Islam Negeri Imam bonjol Padang, 2023)
The main issue in this thesis is how to develop the means of teaching vocabulary for ‎the eighth grade in the Bekunina National Secondary School? The objectives of the ‎research are: to describe the analysis of development needs and to describe the ‎design and development of the means of teaching vocabulary using the Vlog Now ‎application for the eighth grade in the Southern Baconina Solok National ‎Secondary School. D, which consists of definition, design, development, and ‎disseminate. However, the researcher identifies research procedures in development ‎in terms of expert arbitration in terms of the means, language, and materials. As for ‎the results of the developmental research, they are: (1) Analyzing the needs to ‎develop the means of teaching vocabulary using the Vlog now application for the ‎eighth grade in the private secondary school Bikunina, consisting of an analysis of ‎the 2013 curriculum, and the analysis of the Arabic language textbook for the ‎eighth grade in the private secondary school Bikunina Solok South in the semester ‎The first is in teaching vocabulary and analyzing the needs of the Arabic language ‎teacher and analyzing the needs of students based on the data collected from the ‎interview, then developing the means of teaching vocabulary. Using Vlog now for ‎‎8th grade Bikunina National High School Very Needed (2) Vocabulary teaching ‎method design using Vlog now for 8th grade Bikunina Private High School consisted ‎of collecting vocabulary materials, inserting pictures and Vidio Vlog on Vlog now ‎application. Production of the development of the means of teaching vocabulary ‎using the Vlog now application. Expert arbitration for the eighth grade in the ‎private secondary school, Bikunina. As for the result obtained from and the expert ‎arbitration of the method, which is 87.8%, and this is a result that indicates its ‎assessment as “very good”, and the language, which is 8606%, and this is a result ‎that indicates its assessment as “very good”, and for the expert arbitration and the ‎materials, which is 94%, and this is a result that indicates its assessment